Lion of liberty : Patrick Henry and the call to a new nation - Unger, Harlow G., 1931- (Cambridge, MA : Da Capo Press, 2010)
Historian and journalist Harlow Giles Unger chronicles the heroic life of Patrick Henry. One of the most outspoken Founding Fathers, it was Henry who coined the term 'liberty or death, ' and battled tyranny, against the British during the American Revolution. However, he also fought tyranny in America after the war, as he rallied for a Bill of Rights, denounced big government, and instilled in his country an unsurpassed passion for liberty and patriotism
Tongue-tied -- Tongue untied -- The flame is spread -- We are slaves! -- To recover our just rights -- We must fight! -- 'Give me liberty-- ' -- 'Don't tread on me' -- Hastening to ruin -- Obliged to fly -- A Belgian hare -- Seeds of discontent -- On the wings of the tempest -- A bane of sedition -- Beef! beef! beef! -- The sun has set in all its glory.
Includes bibliographical references (pages 287-310) and index.
Keywords: Henry, Patrick, -- 1736-1799.; United States. -- Continental Congress -- Biography; Governors -- Virginia -- Biography; Legislators -- United States -- Biography; Virginia -- History -- Revolution, 1775-1783.; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1789.